Inter-Rater Reliability of the Brazilian Version of the Paykel's Interview for Recent Life Events in a sub-sample of a population-based study. - Tania C. Martinho; Gabriel Graça de Oliveira; Paulo R. Menezes (Universidade de Brasília, 2016)
ackground The Interview for Recent Life Events (IRLE) developed by Paykel is one of the most widely used instruments for assessing life events and its relation to the onset and maintenance of illness. This study aimed to assess the inter-rater reliability of the Brazilian version of this scale in the setting of a population-based case-control study of first episode psychosis in Brazil, considering independent and severe events, the most frequently analysed in psychiatric research. Method Fifteen first episode psychosis cases and 26 controls from the community were assessed simultaneously by two raters using the IRLE. Agreement was measured using percentage of agreement and the weighted kappa (kw). Results There was excellent agreement for occurrence of events (kw=0.90) and month of occurrence (kw=0.96) and moderate agreement for independence (kw=0.51) and objective negative impact (kw=0.68). When considering only independent and severe events, very low values of weighted kappa, contrasting to high values for percentage of agreement, were found. Conclusions The results indicate satisfactory reliability, comparable to those found in international literature. The use of weighted kappa results on a more adequate estimate of reliability, but larger samples are needed to estimate agreement by category of events more precisely.